2022
DOI: 10.1080/14999013.2021.1895377
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Mental Health Practitioners’ Use of Structured Risk Assessment Instruments, Views about Bias in Risk Evaluations, and Strategies to Counteract It

Abstract: The use of structured risk assessment instruments (SRAIs) has increased significantly over the past decades, with research documenting variation between countries. The use of SRAIs, their perceived utility and potential for mitigating bias in forensic risk evaluations (FREs) was investigated in a survey of Dutch forensic mental health practitioners (N ¼ 110) We found generally positive views regarding SRAI utility. Bias in FREs was of concern to respondents. We found no evidence of a bias blind spot (the belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…Although the LS/CMI was originally developed for correctional settings, it has since been shown to measure general criminality among forensic psychiatric populations (Olver & Kingston, 2019). Other forensic tools have also been applied to appraise different types of offending behavior in forensic psychiatric settings (Kamorowski et al, 2022), such as the Psychopathy Checklist–Revised (Hare, 2003), Static-99 (Hanson & Thornton, 1999), Structured Assessment of Violence Risk in Youth (Borum et al, 2002), Sexual Violence Risk–20 (Boer et al, 1997), Spousal Assault Risk Assessment Guide (Kropp et al, 1994), and Guidelines for Stalking Assessment and Management (Kropp et al, 2011). Although the profusion of risk instruments provides forensic clinicians with many options to appraise risk, not all tools are suitable for all forensic settings or populations.…”
Section: Legislative Backgroundmentioning
confidence: 99%
“…Although the LS/CMI was originally developed for correctional settings, it has since been shown to measure general criminality among forensic psychiatric populations (Olver & Kingston, 2019). Other forensic tools have also been applied to appraise different types of offending behavior in forensic psychiatric settings (Kamorowski et al, 2022), such as the Psychopathy Checklist–Revised (Hare, 2003), Static-99 (Hanson & Thornton, 1999), Structured Assessment of Violence Risk in Youth (Borum et al, 2002), Sexual Violence Risk–20 (Boer et al, 1997), Spousal Assault Risk Assessment Guide (Kropp et al, 1994), and Guidelines for Stalking Assessment and Management (Kropp et al, 2011). Although the profusion of risk instruments provides forensic clinicians with many options to appraise risk, not all tools are suitable for all forensic settings or populations.…”
Section: Legislative Backgroundmentioning
confidence: 99%
“…In this review, we include several projects that found evidence of the bias blind spot among forensic mental health experts as well (Neal & Brodsky, 2016; Zapf et al, 2018; Zappala et al, 2018; cf. Kamorowski et al, 2021).…”
Section: What Is Cognitive Bias?mentioning
confidence: 99%
“…We include these adversarial allegiance studies in the current systematic review. We also include other studies measuring forensic mental health experts’ understandings of bias and debiasing strategies (Commons et al, 2004; Kamorowski et al, 2021; MacLean et al, 2019; Neal & Brodsky, 2016) and a couple of studies examining forensic reports for evidence of potential bias (Iudici et al, 2015; Neal, 2018a).…”
Section: What Is Cognitive Bias?mentioning
confidence: 99%
“…Instead, it is common practice to base risk assessments on a screening of the history of psychological disorders and mental health, and to use clinical judgment to estimate the general functioning of mental mechanisms such as perception, cognition, memory, motivation, emotion, and will. In the light of the advantages of empirically validated measures (Kamorowski et al, 2022), various forensic procedures would benefit from access to translated and validated assessment instruments to improve PCS management, treatment, and rehabilitation in the Romanian prison system.…”
mentioning
confidence: 99%